Metal clay magic simple projects for making stunning silver jewellery at home - Dutton, Sara (New Holland Publishers, 2009)
Silver metal clay is a fun and easy-to-use medium that can be shaped and manipulated like clay but fires to become 99.9 per cent metal. This book introduces beginners to the basic techniques of using metal clay, showing how to roll and cut out shapes, set stones and findings, and how to fire, burnish and polish silver.